Acceptance rate of clinical pharmacists' recommendations-an ongoing journey for integration - Orit Peled; Yael Vitzrabin; Eran Beit Ner; Moran Lazaryan; Maya Berlin; Dana Barchel; Matitiahu Berkovitch; Yiftah Beer; Eran Tamir (Frontiers Media S.A., 2023)
Introduction: Multidisciplinary expert team collaboration in the clinical setting, which includes clinical pharmacist involvement can facilitate significant improvements in outcomes and optimize patient management by preventing drug-related problems (DRP). This type of collaboration is particularly valuable in patients with multi-morbidity and polypharmacy such as diabetic foot patients. Evidence regarding the successful integration of a new clinical pharmacist, without previous experience into a unit is still scarce. Therefore, this study aimed to describe and evaluate the actual successful integration process of the clinical pharmacist into a diabetic foot unit by measuring the change in recommendation acceptance rate over time.Methods: A prospective, exploratory treatment effectiveness study based on the recommendation acceptance rate of a new clinical pharmacist introduced into the diabetic foot unit was conducted over a 9- month period. The clinical pharmacist identified medical and drug-related problems (DRP) or any discrepancies in the prescribing and administration of medications. Each identified DRP was documented and formulated as a recommendation by the clinical pharmacist. The main outcome measure was the acceptance rate of recommendations over time.Results: A total of 86 patients, of which 67% were men, averagely aged 66.5 (SD 11.8) years were evaluated. Calculated BMI was 30.2 (SD 6.2). The average number of medical diagnoses was 8.9 (SD3.2), and 11.1 (SD 3.7) prescribed drugs for each patient. Cardiovascular disease was presented by 95% (n = 82) of the patients and 33% of them (n = 28) had uncontrolled hyperglycemia. Averagely, 3.3 (SD 1.9) DRPs were identified pre patient. The efficacy-related DRP recommendation acceptance rate increased over the study period from 37.8% in the first 4 months to 79.4% after a period of 4.75 months. Safety-related DRP recommendation acceptance rate increased from 56% to 67.6%.Conclusion: Improved clinical outcomes and optimized pharmacologic patient management may be achieved by the successful integration of a clinical pharmacist into the team. This study provides evidence of the increasing recommendation acceptance rate of integrated, pharmacist-driven comprehensive medication management in an unexperienced unit. To overcome challenges, team members should collaborate to fully integrate the clinical pharmacist into the team-based structure and utilize proper strategies to minimize and transcend barriers.